How important is the type of working contract for job satisfaction of agency workers? - René Petilliot (Albert-Ludwigs-Universität Freiburg, Forschungszentrum Generationenverträge (FZG), 2016)
Previous research has found that agency workers are less satisfied with their job than regular workers on a perma-nent contract. All these studies have in common that they treat agency workers as a homogeneous group; that is, they did not consider the contract type agency workers hold. This paper analyzes whether differences in job satis-faction can be explained by the contract type using data from the German Socio-Economic Panel. The analysis leads to three main results. First, differences in job satisfaction cannot be explained by the contract type. Second, agency workers on a permanent contract are significantly less satisfied with their job than regular workers on the same contract. Third, agency workers on a fixed-term contract do not differ in reported job satisfaction from reg-ular workers on both fixed-term and permanent contracts. These findings give rise to the hypothesis that as a policy instrument agency employment appears to be well-suited for short-term periods, but it should be prevented that workers are persistently employed in such a work arrangement.
Keywords: C23; I31; J28; J41; 330; Job satisfaction; Temporary agency employment; Fixed-term contracts; Permanent contracts